Analysis of Company Presence on Employee Performance in Remote Areas - Suriaman, Maman; Pasaribu, Veta Lidya Delimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to understand the influence of company presence on employee performance in remote areas, focusing on motivational factors, company support, and challenges faced. Using a qualitative method with a phenomenological approach, data were collected through in-depth interviews and observations of 20 employees at PT. Britmindo operating in Nunukan Regency. Thematic analysis shows that employee performance is influenced by various factors, including company support in the form of special allowances, additional facilities, and training programs tailored to remote area conditions. Employees who feel supported tend to show higher motivation and productivity, despite facing challenges such as limited access to public services and less than optimal work environments. These findings suggest that companies operating in remote areas need to adapt by providing appropriate welfare policies in order to improve employee motivation and performance.